Chinese Eastern Railway in 1920s: Perspectives from ‘Izvestia’ Newspaper - E. O. Starovoytova (Научный диалог, 2024)
This article explores the history of the Chinese Eastern Railway, which spans over 120 years and has significantly influenced the development of Northeast China. The focus of this study is on materials from Soviet press outlets in the 1920s that address Soviet-Chinese relations surrounding the railway. It is noted that following the October Revolution of 1917, the railway became a central point of interaction between Russia and China. The Soviet leadership aimed to establish friendly and equal relations with China while simultaneously seeking to bring the railway’s exclusion zone under Bolshevik control. The objective of this article is to trace how events related to the Chinese Eastern Railway were reported during the transitional period of the 1920s by one of the most authoritative domestic publications — ‘Izvestia’, which has been published since March 1917 and became the official organ of the Central Executive Committee of the USSR after the October Revolution. Through analysis, the article reveals the significant role of ‘Izvestia’ in shaping public perceptions of Soviet-Chinese relations during this period and in conveying Soviet Russia’s Far Eastern policy as a whole.